Conjunctival dysplasia in pterygium – case report - Ljilja Amidžić; Vesna Ljubojević; Radoslav Gajanin; Milka Mavija (Биомедицинска истраживања, 2013)
The study concerns a 65-year-old female patient with pterygium of right eye and histologically verified conjunctival intraepithelial neoplasia. The lesion was diagnosed as pterygium and treated surgically. Histological examination of the excised material found the presence of conjunctival intraepithelial ne oplasia. The significance of this case report is in pointing out the presence of morphological changes in pterygium that may precede the development of squamocellular carcinoma of the conjunctiva and the necessity of histological examination of all excised pterygia.
Keywords: pterygium; conjunctival intraepithelial neoplasia; p53